Multivariable system identification for dynamic discrete-time nonlinear system using genetic algorithm - Ahmad, R.; Jamaluddin, H.; Hussain, Mohd Azlan (2002)
The development of a multivariable system identification model for dynamic discrete-time nonlinear system using genetic algorithm was discussed and analysed. The identification of model structure for a jacketed continuous stirred tank reactor or CSTR was taken as case study. The analysis showed that the proposed genetic algorithm provides an efficient way of determining the model structure of unknown nonlinear systems.